The Effect of Reward Systems and Work Schedule Flexibility on Gen Z Employee Performance with Employee Happiness as an Intervening Variable in Coffee Shops in Bandar Lampung City - Lintang Arum Hapsari; Febrianty; Anita (International Journal of Business and Quality Research, 2026)
This study examines the influence of reward systems and work schedule flexibility on employee performance, with employee happiness as an intervening variable among Generation Z employees in coffee shops in Bandar Lampung. The research adopts a quantitative associative approach using primary data collected from 100 respondents through questionnaires. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that reward systems and work flexibility do not have a direct and significant effect on employee performance. However, both variables have a positive and significant influence on employee happiness, which in turn significantly affects employee performance. Furthermore, employee happiness is proven to mediate the relationship between reward systems, work flexibility, and employee performance. These findings highlight that psychological well-being plays a crucial role in improving employee performance, especially among Generation Z workers. Therefore, organizations should not only focus on external factors such as rewards and flexibility but also prioritize strategies that enhance employee happiness to achieve optimal performance outcomes.